(untitled) (Academia Science Repository, 2023)
Vocabulary learning is an integral aspection in learning a foreign language since the connatations of new words are widely highlighted and is of paramount importance to a language learners. In brief, teaching vocabulary could be affective if teachers follow tips to succers teaching learning process. In this article .I summarizes importance vocabulary and explaining many techniques use by both teacher and leaners what teaching English, when learning English , as well as my teaching activity of these issues.